2022
DOI: 10.3390/life12020147
|View full text |Cite
|
Sign up to set email alerts
|

Resistant Genes and Multidrug-Resistant Bacteria in Wastewater: A Study of Their Transfer to the Water Reservoir in the Czech Republic

Abstract: Wastewater is considered the most serious source of the spread of antibiotic resistance in the environment. This work, therefore, focuses on the fate and spread of antibiotic resistance genes (ARGs) in wastewater and the monitoring of multidrug-resistant strains. ARGs were monitored in the nitrification and sedimentation tanks of the wastewater treatment plant (WWTP) and in the dam into which this WWTP flows, at various times. The highest relative abundance was found for the blaTEM > tetW > blaNDM-1 >… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Previous studies have shown that wastewater samples like wastewater treatment plants can be a source of multidrug-resistant bacteria and antibiotic resistance genes in the environment ( 39 , 40 ). Our study also demonstrates the potential for the spread of mcr-1 from wastewater to human populations.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that wastewater samples like wastewater treatment plants can be a source of multidrug-resistant bacteria and antibiotic resistance genes in the environment ( 39 , 40 ). Our study also demonstrates the potential for the spread of mcr-1 from wastewater to human populations.…”
Section: Discussionmentioning
confidence: 99%
“…Both the microorganisms and enzymes they produce are very good indicators of soil health [ 59 , 91 , 92 , 93 , 94 ], because they are sensitive to various changes proceeding in the environment [ 34 , 59 , 61 ]. The present study results demonstrate that activity of oxidoreductases depended on all variables tested, i.e., soil contamination with tetracycline, soil fertilization with compost, soil sowing with Zea mays , and experiment duration.…”
Section: Discussionmentioning
confidence: 99%
“…According to Conde-Cid et al [ 23 ], antibiotics can be detected in approximately 40% of manures and 17% of soils therein. In addition, the highly hydrophilic character and low volatility of antibiotics make them highly stable in surface and ground waters [ 16 , 34 , 35 ], and even in drinking water [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other antibiotics, such as sulfamethoxazole, could cause mutations in genes and chronic health effects [55]. In general, the presence of antibiotics in the environment can lead to the enhancement of antibiotic-resistant genes and multi-drugresistant microbes that have been part of the global public health crisis [56,57]. Therefore, the removal of these emerging contaminants from wastewater is indispensable.…”
Section: Pharmaceuticals In the Environmentmentioning
confidence: 99%